2024 Cool-Season Forage Variety Recommendations for Florida: SS-AGR-84/AA266, rev. 9/2024 - Wallau, Marcelo; Blount, A. R.; Rios, E.; Vendramini, J. M. B.; Dubeux, J. C. B.; Babar, M. A.; Kenworthy, K. E.; de Souza, C. H.; Quesenberry, K. H. (EDIS, 2024)
This publication provides the most up-to-date information on adapted cool-season forage varieties for our growing season. The recommendation of varieties is based on multi-location, multi-year cultivar evaluation experiments that may include trials in Florida (https://programs.ifas.ufl.edu/forage/technical-information/), Georgia (https://georgiaforages.caes.uga.edu/species-and-varieties/variety-trials/forage-variety-trial-information.html), Alabama (https://aaes.auburn.edu/blog/2024/06/05/winter-forage-summary-tables-2023-2024/), and other states.